2015
DOI: 10.1039/c5dt01786f
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule magnet behaviour in a {Dy4P2} octahedron

Abstract: Two new tetrametallic lanthanide-phosphonate complexes have been structurally and magnetically characterised. The {Dy4} complex is a single molecule magnet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…S5 †). 28,29 Meanwhile, the nonsuperposition of the M vs. H/T plots for 1 and 2 at different temperatures in the high eld further implies that the above mentioned behavior is probably due to the crystal-eld-induced splitting of the Stark level, signicant magnetic anisotropy and/ or low-lying energy states. [30][31][32] In order to investigate the dynamic magnetic properties of compounds 1 and 2, variable frequency alternating current (ac) magnetic susceptibilities were rstly performed with 3 Oe alternating eld and 0 Oe direct current (dc) eld at 2 K. No peaks are observed in the in-phase (c 0 ) vs. v and out-of-phase (c 00 ) vs. v curves for 1 and 2, which may be attributed to the presence of quantum tunneling of magnetization (QTM).…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…S5 †). 28,29 Meanwhile, the nonsuperposition of the M vs. H/T plots for 1 and 2 at different temperatures in the high eld further implies that the above mentioned behavior is probably due to the crystal-eld-induced splitting of the Stark level, signicant magnetic anisotropy and/ or low-lying energy states. [30][31][32] In order to investigate the dynamic magnetic properties of compounds 1 and 2, variable frequency alternating current (ac) magnetic susceptibilities were rstly performed with 3 Oe alternating eld and 0 Oe direct current (dc) eld at 2 K. No peaks are observed in the in-phase (c 0 ) vs. v and out-of-phase (c 00 ) vs. v curves for 1 and 2, which may be attributed to the presence of quantum tunneling of magnetization (QTM).…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…Previous studies have shown that the phosphonate moiety is an efficient functional group for the construction of molecular cages [38,39]. Winpenny and co-workers reported results using t-butylphosphonic acid (H2O3P t Bu) reacted with lanthanide salts Ln(NO3)3·nH2O or lanthanide pivalates (Ln = Gd(III), Tb(III), Dy(III), Ho(III), and Er(III) [12,13,39]. Winpenny and coworkers have also synthesized a decanuclear 3d-4f phosphonate cage of [Co4Ln10(O2C t Bu)12(O3PC6H10NH2)8(PO4)2(O2CMe)2(O3PC6H10NH3)2] (Ln = Gd, Dy) [38].…”
Section: Syntheses Of the Complexesmentioning
confidence: 99%
“…4f-phosphonate molecular cages have been studied because of the magnetic anisotropies of the lanthanide ions and the weak coupling between the metal ions can produce interesting properties [12]. When the isotropic Gd(III) metal ion is present, lanthanide phosphonate clusters display impressive magnetocaloric effects (MCE), which have been suggested for application in magnetic refrigeration [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the arrangement of magnetic axes could be related to the dynamic magnetic behavior in both the compounds. 31 This result emphasizes that one needs to consider more on the negative charges of the coordination atoms for the rational design of lanthanide SMMs in a specific symmetry.…”
mentioning
confidence: 95%